1997
DOI: 10.1212/wnl.49.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Central poststroke pain and Wallenberg's lateral medullary infarction: Frequency, character, and determinants in 63 patients

Abstract: CPSP developed in 25% (16/63) of the patients, all within 6 months. This was constant and severe with frequent allodynia, but responded in all cases to amitriptyline and recurred promptly on attempted weaning. CPSP affected the ipsilateral peri-orbital region most commonly, either alone or in combination with the contralateral limbs. Ipsilateral neurotrophic facial ulceration developed in two cases. CPSP correlated significantly (Fisher's exact test, p < 0.0002) with the degree of clinical sensory loss but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
2
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(92 citation statements)
references
References 11 publications
(14 reference statements)
4
78
2
8
Order By: Relevance
“…As a result, thalamic lesions were thought to be required for development of pain, and the syndrome was referred to for decades by the misleading term "thalamic pain." Research since that time has established that CPS can result from damage to any structure along spinothalamo-cortical pathways that convey pain and temperature information (Boivie 2005;Bowsher 1996;Finnerup et al 2003;Kim et al 2007;MacGowan et al 1997;Peyron et al 2000;Schmahmann and Leifer 1992).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, thalamic lesions were thought to be required for development of pain, and the syndrome was referred to for decades by the misleading term "thalamic pain." Research since that time has established that CPS can result from damage to any structure along spinothalamo-cortical pathways that convey pain and temperature information (Boivie 2005;Bowsher 1996;Finnerup et al 2003;Kim et al 2007;MacGowan et al 1997;Peyron et al 2000;Schmahmann and Leifer 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, LEPs are inappropriate to reflect the slowly emerging, ill-defined and long-lasting phenomena that underlie over-reaction symptoms (hyperalgaesia and allodynia), which are thought to depend on spino-reticulo-thalamic projection systems. [31][32][33] In other words, the slope of energy change associated to allodynic or hyperalgaesic symptoms is commonly not abrupt enough to generate LEPs. Thus, LEPs accurately reflect the spinothalamic deafferentation leading to pain discrimination deficits, but do not index the neural events underlying allodynia and hyperalgaesia.…”
Section: Nature Of the Painmentioning
confidence: 99%
“…44 This figure increases to 25-60% in syringomyelia or brainstem infarcts. 33,37 As pain usually does not develop immediately but commonly one to six months after the triggering event, preventative therapy may be attempted early if we could reliably determine those patients prone to develop neuropathic pain.…”
Section: Laser-evoked Potentials Abnormalities Depend On Both Lesion mentioning
confidence: 99%
“…[2][3][4][5] To date, the largest prospective study, which enrolled 15 754 participants with ischemic stroke from 35 countries, found that 2.7% of patients developed CPSP at 1 year after stroke.…”
mentioning
confidence: 99%